Managing complex projects and programs how to improve leadership of complex initiatives using a third-generation approach - Heaslip, Richard J., 1955- (John Wiley & Sons, Inc., 2014)
"Focuses on aligning projects and programs within the complex environments of today's business models"-- Provided by publisher